Depression Following Thrombotic Cardiovascular Events in Elderly Medicare Beneficiaries: Risk of Morbidity and Mortality - Christopher M. Blanchette; Linda Simoni-Wastila; Fadia T. Shaya; Denise Orwig; Jason Noel; Bruce Stuart (Cardiology Research and Practice)
Purpose. Depression and antidepressant use may independently increase the risk of acute myocardial infarction and mortality in adults. However, no studies have looked at the effect of depression on a broader thrombotic event outcome, assessed antidepressant use, or evaluated elderly adults. Methods. A cohort of 7,051 community-dwelling elderly beneficiaries who experienced a thrombotic cardiovascular event (TCE) were pooled from the 1997 to 2002 Medicare Current Beneficiary Survey and followed for 12 months. Baseline characteristics, antidepressant utilization, and death were ascertained from the survey, while indexed TCE, recurrent TCE, and depression (within 6 months of indexed TCE) were taken from ICD-9 codes on Medicare claims. Time to death and first recurrent TCE were assessed using descriptive and multivariate statistics. Results. Of the elders with a depression claim, 71.6% had a recurrent TCE and 4.7% died within 12 months of their indexed TCE, compared to 67.6% and 3.9% of those elders without a depression claim. Of the antidepressant users, 72.6% experienced a recurrent TCE and 3.9% died, compared to 73.7% and 4.6% in the subset of selective serotonin reuptake inhibitor (SSRI) users. Depression was associated with a shorter time to death (P=.008) in the unadjusted analysis. However, all adjusted comparisons revealed no effect by depression, antidepressant use, or SSRI use. Conclusions. Depression was not associated with time to death or recurrent TCEs in this study. Antidepressant use, including measures of any antidepressant use and SSRI use, was not associated with shorter time to death or recurrent TCE.